Occurrence and Nomenclature of a Rare Bamboo Neomicrocalamus manii - Naithani, H. B. (Indian Forester, 1994)
A rare bamboo Neomicrocalamus manii(Gamb1e) Majumdar so far known from Meghalaya and Arunachal Pradesh, India has now been collected after a lapee of 62 years. In Arunachal Pradesh it is called Tagir or Tager by Adi, Nishi and Tagin people.